Kinetically Controlled Site-Specific Self-assembly of Hairy Colloids - Vazirieh Lenjani, Shayan (Langmuir : the ACS journal of surfaces and colloids, 2024)
The solvophobicity-driven directional self-assembly of polymer-coated gold nanorods is a well-established phenomenon. Yet, the kinetics of this process, the origin of site-selectivity in the self-assembly, and the interplay of (attractive) solvophobic brush interactions and (repulsive) electrostatic forces are not fully understood. Herein, we use a combination of time-resolved (vis/NIR) extinction spectroscopy and finite-difference time-domain (FDTD) simulations to determine conversion profiles for the assembly of gold nanorods with polystyrene shells of distinct thicknesses into their (tip-to-tip) self-assembled structures. In particular, we demonstrate that the assembly process is highly protracted compared with diffusion-controlled rates, and we find that the assembly rate varies for different thickness values of the polymer shell. Our findings were rationalized using coarse-grained molecular dynamics simulations, which also corroborated the tip-to-tip preference in the self-assembly process, albeit with a uniform polymer coating. Utilizing the knowledge of quantified conversion rates for distinct colloidal species, we designed coassembling systems with different brush thicknesses, featuring "narcissistic" self-sorting behavior. This provides new perspectives for high-level supracolloidal self-assembly